Penerapan Sikap Kerja, Komitmen Kerja, dan Stres Kerja Dalam Meningkatkan Kinerja Pegawai Pada Kantor Urusan Agama - Siti Widya Wulandari; Ramadan; Deddiarto Bangkit Hasudungan Hutauruk; Daulat Parlaungan; Claudius Romual Nauli Siburian; Nurdiana Nasution; Eddi Suprayitno (Journal of Trends Economics and Accounting Research, 2023)
The problem formulation in this research is how to apply work attitudes to improve performance. How to apply work commitment to improve performance. How to apply work stress to improve performance. How to apply work attitudes, work commitment and work stress in improving performance. The aim of this research is to determine and analyze the application of work attitudes in improving performance. To find out and analyze the application of work commitment in improving performance. To find out and analyze the application of work stress in improving performance. To find out and analyze the application of work attitudes, work commitment and work stress in improving performance. The sample in this study consisted of 36 employees. The data analysis technique in this research uses descriptive analysis and multiple linear regression analysis. The results of this research explain that work attitude has a positive and significant effect on improving performance. Work commitment has a positive and significant effect on improving performance. work stress has a positive and insignificant effect on improving performance. work attitude, work commitment and work stress in improving performance.